2015
DOI: 10.1378/chest.14-2434
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of COPD in the Presence of Comorbidities

Abstract: BACKGROUND:The morbidity and mortality associated with COPD exacts a considerable economic burden. Comorbidities in COPD are associated with poor health outcomes and increased costs. Our objective was to assess the impact of comorbidities on COPD-associated costs in a large administrative claims dataset.METHODS:This was a retrospective observational study of data from the Truven Health MarketScan Commercial Claims and Encounters and the MarketScan Medicare Supplemental Databases from January 1, 2009, to Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
126
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 21 publications
(26 reference statements)
11
126
0
6
Order By: Relevance
“…Data from a large claims database (Truven Health MarketScan Commercial Claims and Encounters and the MarketScan Medicare Supplemental Databases) showed that COPD- or asthma-related total health-care costs were greatest among patients with COPD and asthma and CKD ($41,288 for the first year after the diagnosis of CKD). Our results add to the existing literature about the mortality burden among this population and argue for further studies to elucidate the important clinical factors associated with COPD among those with CKD(26). …”
Section: Discussionsupporting
confidence: 68%
“…Data from a large claims database (Truven Health MarketScan Commercial Claims and Encounters and the MarketScan Medicare Supplemental Databases) showed that COPD- or asthma-related total health-care costs were greatest among patients with COPD and asthma and CKD ($41,288 for the first year after the diagnosis of CKD). Our results add to the existing literature about the mortality burden among this population and argue for further studies to elucidate the important clinical factors associated with COPD among those with CKD(26). …”
Section: Discussionsupporting
confidence: 68%
“…However, beyond the simple co-occurrence of two diseases, recent research efforts have proved that there are unique interactions between COPD and certain specific chronic conditions. Some diseases could influence COPD outcomes (disease progression and exacerbation frequency), including higher costs [4] and mortality [5]; other diseases could be present selectively among a unique subgroup of COPD (currently described as phenotypes) [6]; and, finally, the presence of some chronic conditions could influence decisions about COPD management. In this article, we will review the current knowledge about frequency and mechanisms responsible for the most common COPD comorbidities, and recent advances in the field.…”
Section: Introductionmentioning
confidence: 99%
“…2 departamento de economía aplicada de la universidad de Murcia, Murcia, españa. 3 instituto de actividad Física, salud y calidad de vida. universidad autónoma de chile.…”
unclassified
“…El impacto epidemiológico, social y económico de la EPOC es enorme. Se espera que sea la causante del 7,8% del total de muertes, la cuarta causa de muerte en el mundo en 2030 2 y suponiendo una carga económica sustancial 3 . Los pacientes que sufren EPOC a menudo tienen una mala calidad de vida relacionada con la salud (CVRS), incluso al inicio de la enfermedad 4 debido a sus síntomas, a la reducción en la capacidad de realizar actividades de la vida diaria y al uso de medicamentos.…”
unclassified